A novel iron phosphate cement derived from copper smelting slag and its early age hydration mechanism. (October 2022) - Luo, Yunlong; Zhou, Xintao; Luo, Zhongqiu; Ma, Hongyan; Wei, Yu; Liu, Qin
Abstract: Copper slag (CS), a by-product of copper smelting, is normally stockpiled, leading to wastes of resource and space as well as environment pollution. It has not been massively reutilized as a supplementary cementitious material in Portland cement due to its low reactivity. In the present study, CS is for the first time utilized as the base component to prepare an iron phosphate cement (IPC) by reacting with ammonium dihydrogen phosphate (ADP) at room temperature. The influence of the raw materials mass ratio (CS/ADP) on the microstructure and performance of IPC pastes are investigated. It is found that the compressive strength of IPC pastes at all ages is not a monotonic function of CS/ADP, and the paste with CS/ADP of 2.0 gives the highest strengths, i.e., 26.8, 38.9 and 47.5 MPa at 1, 3 and 28 d, respectively. The crystalline phases including FeH2 P3 O10 ·H2 O and FePO4 are formed as the main reaction products to bind the unreacted CS particles. The early age hydration of IPC is found to be a multi-stage process, involving the initial dissolution of ADP and iron-containing phases of CS, the formation of FeH2 P3 O10 ·H2 O, the initial generation of FePO4, and the attainment of the hydration reaction equilibrium. Unlike the magnesium phosphate cement, a redox reaction of Fe(Ⅱ) into Fe(Ⅲ) occurs due to the suitable range of pH and oxidation-reduction potential of the IPC system during the hydration reaction. Highlights: A novel iron phosphate cement (IPC) was firstly prepared using copper slag as the base source. The raw materials ratio (CS/ADP) has great impacts on the property of IPC paste. A redox reaction of Fe(Ⅱ) into Fe(Ⅲ) occurs during the hydration reaction of IPC. The crystalline phases of FeH2 P3 O10 ·H2 O and FePO4 are formed as the main hydration products.